DEVELOPMENT OF INTERACTIVE TEACHING MATERIALS WITH RME-BASED ISPRING SUITE TO IMPROVE STUDENTS' CREATIVE THINKING SKILLS - Pradja, Barra P; Saputra, Nisvu Nanda; Baist, Abdul; Andriyani, Retno; Saleh, Hairul; Iskandar, Ratu Sarah Fauziah (Jurnal Pendidikan Matematika (JUPITEK), 2024)
With the use of the RME-based iSpring suite, this project creates interactive teaching resources to enhance students' capacity for creative thought. Students' low capacity for creative thought, low levels of desire, low levels of activity, and low levels of involvement in the learning process are the field's problems. In order to address these issues, interactive instructional resources were created. With the help of RME-based ispring suites, interactive teaching materials will be created that are valid, useful in the educational process, and will enhance students' capacity for creative thought. 4D (define, design, development, disseminate) is the development model that is employed. Pretest-poste instruments, student response questionnaires, and validation sheets are used in data gathering procedures. Analysis methods include the paired sample t-test, validity test, and practicality test, n-gain test. With a score of 3.41, the validity test results indicate that the product is already in the legitimate category. According to the analysis of the practicality test results, the produced product already has a score of 3.43, placing it in the extremely practical category. It is established by the paired sample t-test that capacity differences exist between pre- and post-use of interactive training resources. Moreover, improving pupils' capacity for creative thought is known to fall into the effective group based on the results of the n-gain test. In order for the RME-based iSpring suite of interactive teaching resources to be generally appropriate for use in the learning process